Effectiveness of the Superitem Learning Model on Students Learning Achievements - Ikawati, Hastuti Diah; Majid, Ilham Abdul; Anwar, Zul (International Journal for Educational and Vocational Studies, 2019)
Student activeness in class is one of the important factors that influence student learning outcomes. This activity can be influenced by several factors one of the learning models used by lecturers. The lack of variations in the learning model has an impact on the monotonous learning process so that students are easily bored and bored with the learning process. Therefore, lecturers are always required to create an interesting learning condition process, including by applying a varied learning model. There are several learning models that can be used by lecturers to improve student learning outcomes, one of which is to implement super-learning learning models. The purpose of this study was to determine the effect of super-learning models on student learning outcomes in the course of the Diffusion of Educational Innovation. The population of this study is all Education Technology students who have programmed the Education Innovation Diffusion course in the even semester of the 2018/2019 academic year. Data collection techniques used tests to determine the differences in student learning outcomes before and after the super-learning learning model was used — data analysis using t-test formula. Based on the results of the study it is known that the results of the t-test show the value of t-count greater than t-table at a significance level of 5% with db = 30-1 = 29 (12,963> 2,045). Based on the results of the calculation it can be concluded that it can be concluded, there is the influence of the Superitem learning model on student learning outcomes in the educational innovation diffusion course in Education Technology Study Program Mataram IKIP academic year 2018/2019.